Coping Strategies of Students Experiencing Social Anxiety in the Academic Context - Hakim, Naufal; Ichlasniate Katiara Maghfira; Pramudya Bagus Wirayudha; Cut Rauzatul; Umi Fadhillah Zahwa Salsabila; Irin Riamanda (Jurnal Psikologi Terapan, 2025)
This study aims to explore the subjective experiences of students with social anxiety in academic contexts, as well as the coping strategies they employ to manage it. Social anxiety refers to a form of anxiety that arises from the fear of negative evaluation in social interactions. In academic settings, this often manifests in situations such as presentations, group discussions, or communication with lecturers. A qualitative approach with a narrative method was employed. Five active university students who experienced symptoms of social anxiety were selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic-narrative analysis. The findings revealed that students experienced both physical symptoms (e.g., cold hands, heart palpitations, and sleep disturbances) and cognitive symptoms (e.g., overthinking and excessive fear of judgment). The coping strategies identified were categorized into two main types: problem-focused coping, such as practicing presentations and preparing scripts, and emotion-focused coping, such as praying, sharing with friends, and self-reflection. Some respondents also reported using avoidance strategies, such as skipping presentations due to feeling unprepared.